MILLENIUM DEVELOPMENT GOAL (MDG) AND NATIONAL DEVELOPMENT PROGRAM IN INDONESIA - Loetan, Syahrial (Indonesian Journal of International Law, 2021)
The adoption of the Millenium Development Goals (MDG) in the Millenium Summit in 2000 by all 189 member of the UN General Assembly was a defining moment for global cooperation in the 21st century. The MDG is global framework to face the challanges regarding human resources development in the world. In the Indonesian context, the question is: “do targets and indicators contained in MDG have accorded with domestic values ?” the question is relevant because the MDG will never be achieved if the MDG does not accomodate local values. Localization of the MDG must be first step to take in achieving MDG for each country. Refer to the recent condition in Indonesia, there are several problems in achieving MDG targets such as: (i) quality of human resources, (ii) infrastructure, (iii) implementation of the decentralization, (iv) slow economy recovery, (v) law enforcement, and (vi) existence of several conflict regions. Based on those conditions, achieving the targets and indicators of MDG in Indonesia is not easy. Collective effort involving international community like donors and national community like civil society, business or private sector and universities is a must.